PENGARUH TEMPORAL JANGKA PANJANG GREEN HUMAN RESOURCE MANAGEMENT TERHADAP KINERJA ORGANISASI BERKELANJUTAN: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Bayu Aji Pramudia; Roby Sambung; Hendra Saputra; M. Sagif Atha Zain; Jans William Beltsa Jarias; Choudias Rehuel (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The increasing demand for sustainable business practices has encouraged organizations to integrate environmental aspects into human resource management through Green Human Resource Management (GHRM). GHRM is regarded as a strategic approach that supports the achievement of sustainable organizational performance by fostering environmentally friendly behavior, green organizational culture, and a commitment to sustainability. This study aims to analyze and synthesize previous research findings regarding the long-term impact of GHRM on sustainable organizational performance. The study employs a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. The reviewed articles were obtained from various reputable international databases and were published between 2020 and 2026. The review process included identification, screening, eligibility assessment, and thematic analysis of relevant literature. The findings indicate that GHRM contributes positively to improving organizations’ environmental, social, and economic performance. Practices such as green recruitment, green training and development, green performance management, green compensation, employee involvement, and the implementation of green workplace environments have been shown to enhance employees’ environmentally friendly behavior, work engagement, organizational commitment, and sustainability culture. Furthermore, leadership support, organizational culture, and commitment to sustainability serve as reinforcing factors in the relationship between GHRM and sustainable organizational performance. This review confirms that the integration of GHRM is a crucial strategy for supporting organizational sustainability transformation and provides direction for the development of future longitudinal research.